DAMPAK OPERASIONALISASI PEMBANGUNAN WATER TREATMENT PLAN (WTP) SPAM PASIGALA TERHADAP LAHAN PERTANIAN MASYARAKAT DESA OLOBOJU KABUPATEN SIGI - Tabanal, Ferawati S. (Katalogis, 2017)
This research aims to find out the operational impact of Pasigala SPAM development on agricultural land of Oloboju village of Sigi Regency of Central Sulawesi. The theory used is the theory of â€œLand Rentâ€ proposed by Ricardo which consists of several factors that serve as a benchmark. The assumption used in Ricardoâ€™s theory is a fertile area, where the land is used only for farming and subsistence. One important feature in the development of agricultural areas is the need for a vast land area and meets the scale of the economy. Rent will arise if there is an increase in the number of population and increased demand for land, so that the value of rent is influenced by the quality of the land. Increase in the number of population one of them is the absorption of labor that became one factor/impact of the operational of the Pasigala SPAM. This research used descriptive explorative method. Data were collected through interviews, documentation, document review and observation. Respondent was determined by applying purposive sampling. Data were analyzed by interactive analysis with its component that is data reduction, data presentation, and conclusion. The result of the research reveal that the impact of operational Pasigala SPAM on the agricultural land of Oloboju villagers is quite significant, among others: (1)The need for land as one of the important characteristics in the development of agricultural areas and meet the economic scale. (2) Land quality according to Land Rent theory that rent value is influenced by land quality. (3) The increase of peopleâ€™s income due to the absorption of manpower. (4) The absorption of labor due to the development of Pasigala SPAM, but not always have direct impact. (5) Employment alse affects the emergence of economic activities with the creation of new job sources. (6) The emergence of economic activity and new job sources allows increased demand for new land. (7) The higher demand for the land will at times threaten the quality of the land and at times will change the function due to land conversion. (8) The impact of externalities that appears both positive and negative.